2015
DOI: 10.1063/1.4935539
|View full text |Cite
|
Sign up to set email alerts
|

Efficient nanorod-based amorphous silicon solar cells with advanced light trapping

Abstract: We present a simple, low-cost, and scalable approach for the fabrication of efficient nanorod-based solar cells. Templates with arrays of self-assembled ZnO nanorods with tunable morphology are synthesized by chemical bath deposition using a low process temperature at 80 °C. The nanorod templates are conformally coated with hydrogenated amorphous silicon light absorber layers of 100 nm and 200 nm thickness. An initial efficiency of up to 9.0% is achieved for the optimized design. External quantum efficiency me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The simulated results (Figure S3) exhibit that relatively poor (average absorbance below 70%) and narrow bandwidth absorptions were obtained in the UV–vis spectral range, with low densities and small areas of E-field distributions surrounding the Au NCs or Au film (see the insets a and b of Figure S3) due to the lack of the multiple surface plasmon resonances. In addition, it is important to point out that the “V”-shaped structures from Au NCs induced a positive light-trapping effect to reduce the incident surface reflection, , which would be conducive for designing MAs with excellent absorption properties. Specifically, the Au NCs present hierarchical architectures, which are composed of many “V”-shaped branches reaching in different directions.…”
Section: Resultsmentioning
confidence: 99%
“…The simulated results (Figure S3) exhibit that relatively poor (average absorbance below 70%) and narrow bandwidth absorptions were obtained in the UV–vis spectral range, with low densities and small areas of E-field distributions surrounding the Au NCs or Au film (see the insets a and b of Figure S3) due to the lack of the multiple surface plasmon resonances. In addition, it is important to point out that the “V”-shaped structures from Au NCs induced a positive light-trapping effect to reduce the incident surface reflection, , which would be conducive for designing MAs with excellent absorption properties. Specifically, the Au NCs present hierarchical architectures, which are composed of many “V”-shaped branches reaching in different directions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ZnO nanostructures have been employed on various solar cells to impart AR properties (amorphous-Si [284,285], sc-Si [286][287][288], mc-Si [289], GaAs [290]). Lin et al deposited syringe-shaped ZnO nanorods on multi-crystalline silicon photovoltaic cells by a two-step aqueous solution process and obtained an efficiency enhancement of nearly 41% with a value of 17.61% when compared to those of bare surface [172].…”
Section: Multi-crystalline Silicon Solar Cellsmentioning
confidence: 99%
“…Therefore, increasing the optical path length in the absorbing layer causes an increase in light absorption. However, this method cannot easily control the surface structure morphology, which limits its future development [19]. Many studies have reported the use of a ZnO nanostructure for applications in devices.…”
Section: Introductionmentioning
confidence: 99%